Antibacterial activity of β-sitosterol isolated from the leaves of Odontonema strictum (Acanthaceae). (15th September 2021) - Pierre Luhata, Lokadi; Usuki, Toyonobu
Graphical abstract: Abstract: The observation of a dog eating the roots of Odontonema strictum in 2008 in Lubumbashi (DR. Congo) was the starting point of this research which later led to the isolation of β-sitosterol (BSL), a known phytosterol, isolated for the first time from the leaves of this tropical plant which has a large range of medicinal properties including anti-inflammation, anti-hypertension and antibacterial. The analysis of the 1 H NMR spectrum showed that the active compound contains 60% of BSL and 40% of stigmasterol. With a melting point (m.p.) of 134–136 °C and the Rf value 0.55 in EtOAc-hexane (1:3) on silica gel TLC, the active compound was confirmed to be BSL. Here, we determined the minimal inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of BSL on Staphylococcus aureus by the broth dilution method. The MIC and MBC were found to be 1.24 mg/mL and 2.208 mg/mL, respectively. For the crude extract, the MIC and MBC were 4.33 mg/mL and the MBC was 7.66 mg/mL, respectively. The Total antibacterial activity underlined the fact that the crude extract from 1 g of plant materials could be diluted 65 times and still retains the ability to inhibit the growth of S. aureus . This is the first report of the antibacterial activity of BSL from this plant.